Metodología para la ubicación del sensor de emisión acústica en una caja de engranajes (2019)
The purpose of this document is to identify the best position of an acoustic emission sensor in a gearbox for fault detection. The acoustic emission sensor was located in the four side walls of the gearbox, where three signals were acquired in each position to be analyzed in the time domain by condition indicators and finally the best signals were analyzed in the frequency do-main by means of the gear step frequency. As a result, it was obtained that the sensor must be positioned in the shorter length lateral parts of the gearbox